2017
DOI: 10.17116/jnevro20171179143-50
|View full text |Cite
|
Sign up to set email alerts
|

Results of multicenter study of efficacy and safety of divaza in the treatment of the asthenic and mild to moderate cognitive disorders in elderly and senile subjects

Abstract: The efficacy and safety of divasa in asthenic and mild to moderate cognitive disorders in elderly and senile subjects were shown. There is a need for a multicenter placebo-controlled trial on the efficacy of divasa to treat cognitive and asthenic disorders in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Prespeci ed secondary end points: the proportion of patients with a decrease in the total score of the MoCA questionnaire by 1 or more points in the Divaza group will be at least 82%, while in the placebo group, the same indicator will be no more than 50% [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prespeci ed secondary end points: the proportion of patients with a decrease in the total score of the MoCA questionnaire by 1 or more points in the Divaza group will be at least 82%, while in the placebo group, the same indicator will be no more than 50% [29].…”
Section: Discussionmentioning
confidence: 99%
“…The following reaction parameters were analyzed: rapid CL are amplitude (mV) re ecting the level of preformed LPO products (mainly lipid hydroperoxides); duration of CL latent period (seconds) characterizing LP resistance to oxidation, which re ects the level of endogenous antioxidant potential, and the maximum intensity of chemiluminescence (mV) re ecting LP oxidation capacity [29].…”
Section: Sample Handling and Analysismentioning
confidence: 99%
“…The study confirmed the high safety profile of Divaza. Previous studies showed the ability of Divaza to improve the health state, the QoL, and sleep pattern of patients with vestibular disorder, asthenic syndrome, and CD [9, 17].…”
Section: Discussionmentioning
confidence: 99%
“…S100B is a protein primarily expressed by astrocytes and involved in regulation of neurogenesis in the developing and adult brain [16]. The combined endothelial protective and nootropic effects of Divaza components cause improvement of cognitive functions in patients with cerebrovascular diseases [9, 17]. Thus, Divaza possesses a polyvalent mechanism of action (affecting the trophic processes, neuroprotection, and neuroplasticity) and has a favorable safety profile, which allows using the medicine in elderly patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotective action of the combination of RAF Abs to S100 and RAF Abs to eNOS was shown in a trial, conducted by Parfenov et al: a 10% decrease in asthenia severity in 61% of patients, threefold decrease in 25% of patients, and improvement in sleep and quality of life (according to the SF36 questionnaire) were shown 192…”
Section: Treatment Of Vci and Perspectives Of A Novel Preparationmentioning
confidence: 97%